INSTITUSIONALISASI KERJASAMA AMERIKA SERIKAT - NEGARA LEMBAH BAWAH MELALUI PEMBENTUKAN LOWER MEKONG INITIATIVE 2009-2013 - Putri, Jovita Aditya; Windiani, Reni; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The damming Mekong River by China is a transnational environmental crime that hasbeen causing severe environmental, health, education, food security, and human securitydamages, especially affecting the lives of Lower Mekong Countries which consist ofThailand, Lao People's Democratic Republic, Cambodia, Vietnam, and Myanmar. Seeingthat problem, United States came with help by establishing an institution called LowerMekong Initiative in 2009 which cooperate under environment and water, health,education, connectivity, and women empowerment pillars. The goal of this research is tofind out how the United States has been helping solve the problems in Lower MekongCountries by Lower Mekong Initiative establishment under Obama's era in 2009-2013. Inorder to answer that question, this research used the Neoliberal Institutionalization andInternational Cooperation Theory. The method that used in this research is a qualitativemethod with descriptive-analytical type which done by interviews and literatures review.The result from this research is that the United States has role as initiator, donor, trainingfacilitator, donor assistance, and facilitator of regional dialogue in establishing LowerMekong Initiative. The recommendation that writer addressed to Lower Mekong Initiativeis to make an annual report regarding the result of this cooperation in the membercountries and address China to give transparency about dam data and to reassess the damas to meet the decent international standard of good dam management.